(untitled) (Fiep Bulletin - online, 2019)
Daily the number of people looking for gyms to aid in the search for the desired aesthetic standard increases. With theincreasing demand for bodybuilding, the use of ergogenics has also increased, aiming to maintain health or even improve sportsperformance. The objective of the present study was to verify the incidence of ergogenic use and to characterize the bodybuildingindividuals who use ergogenic substances and to verify which professional is prescribing these substances. A total of 164bodybuilders were evaluated. The participants answered a questionnaire elaborated in Google Docs with the theme about theuse of ergogenic substances. The questions applied followed objective and multiple choice. Based on the data presented, it isconcluded that the use of steroids is not so common among bodybuilders, but their prescription does not happen due to the factthat in no case was there a medical prescription. With regard to supplements, its use is very common, for the various objectives,however, it is not frequent the indication made by a nutritionist. From the analysis of the data, it is noticed that there is even theintervention of Physical Education Professionals, which is not in accordance with the functions they must exercise, emphasizingthat each professional should act in the area in which he is responsible formation.